Predictive factors of body weight loss in patients with type 2 diabetes treated with GLP-1 receptor agonists: a 52-week prospective real-life study - Vozza, Alfredo; Triggiani, Domenico; Fanelli, Margherita; Lisco, Giuseppe; Coletto, Deborah; Custodero, Carlo; Volpe, Sara; Racaniello, Davide; Colaianni, Valentina; Lavarra, Valentina; Maggipinto, Rosselia; Portacci, Andrea; et al. (Frontiers in Endocrinology, 2025)
IntroductionGlucagon-like peptide-1 receptor agonists (GLP-1RAs) are widely prescribed for their efficacy in glycemic control and weight reduction, but patient response is heterogeneous and predictors of weight loss remain insufficiently defined. This 52-week prospective, observational study aimed to identify predictors of weight reduction (≥5% from baseline) in patients with type 2 diabetes mellitus (T2D) undergoing GLP-1RA therapy (semaglutide or dulaglutide, including oral formulations).MethodsA total of 194 adults with T2D initiating GLP-1RA therapy were evaluated at baseline, and after 6, and 12 months of therapy. To identify predictors of weight loss, variables differing between Responders (weight loss ≥5% than baseline) and Non-Responders were evaluated by ROC analysis and tested in univariate and multivariate logistic regression models adjusted for age, gender, GLP-1RA type and dosage.ResultsAt 6 and 12 months, 58% and 49% of patients, respectively, achieved the primary outcome. Responders at 12 months exhibited elevated BMI, waist circumference, hepatic steatosis indices, fat mass, and insulin levels at baseline, along with reduced muscle-to-fat and muscle-to-visceral adipose tissue ratios. Moreover, female gender, younger age, shorter disease duration, and non-use of metformin prior to enrollment were significantly associated with response. Notably, early response at 6 months strongly predicted 12-month success.ConclusionsOur results highlight a valuable interplay between body composition, liver involvement, and the incretin response, also suggesting a maximal synergistic effect between metformin and GLP-1RAs when treatments are initiated concurrently rather than sequentially. These data provide valuable insights for the development of individualized treatment strategies.